Parkinson’s Disease and α-synuclein Expression - Devine, Michael J. (Mov Disord, 2011)
Genetic studies of Parkinson’s disease over the last decade or more have revolutionized our understanding of this condition. α-Synuclein was the first gene to be linked to Parkinson’s disease, and is arguably the most important: the protein is the principal constituent of Lewy bodies, and variation at its locus is the major genetic risk factor for sporadic disease. Intriguingly, duplications and triplications of the locus, as well as point mutations, cause familial disease. Therefore, subtle alterations of α-synuclein expression can manifest with a dramatic phenotype. We outline the clinical impact of α-synuclein locus multiplications, and the implications that this has for Parkinson’s disease pathogenesis. Finally, we discuss potential strategies for disease-modifying therapies for this currently incurable disorder.